2019
DOI: 10.1101/631150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allelic imbalance reveals widespread germline-somatic regulatory differences and prioritizes risk loci in Renal Cell Carcinoma

Abstract: Determining the function of non-coding regulatory variants in cancer is a key challenge transcriptional biology. We investigated genetic (germline and somatic) determinants of regulatory mechanisms in renal cell carcinoma (RCC) using H3K27ac ChIP-seq data in 10 matched tumor/normal samples and RNA-seq data from 496/66 tumor/normal samples from The Cancer Genome Atlas (TCGA). Unsupervised clustering of H3K27ac activity cleanly separated tumor from normal individuals, highlighting extensive epigenetic reprogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 65 publications
2
19
1
Order By: Relevance
“…13 The behavior and performance of CAVIAR is representative of similar QTL-based methods such as CAVIARBF, FINEMAP, and PAINTOR without functional annotation data. [14][15][16] The versions of PLASMA are furthermore compared against the only other publicly released fine-mapping method (to our knowledge) that integrates AS data described in the pre-print of Zou et al 24 This unnamed method, denoted as ''AS-Meta,'' utilizes the association between SNP heterozygosity and a binary indicator of allelic imbalance. By binarizing allelic imbalance, AS-Meta is expected to lose power relative to treating imbalance as a quantitative phenotype but may be more robust to spurious AS signal.…”
Section: Comparison Of Existing Models With Plasmamentioning
confidence: 99%
“…13 The behavior and performance of CAVIAR is representative of similar QTL-based methods such as CAVIARBF, FINEMAP, and PAINTOR without functional annotation data. [14][15][16] The versions of PLASMA are furthermore compared against the only other publicly released fine-mapping method (to our knowledge) that integrates AS data described in the pre-print of Zou et al 24 This unnamed method, denoted as ''AS-Meta,'' utilizes the association between SNP heterozygosity and a binary indicator of allelic imbalance. By binarizing allelic imbalance, AS-Meta is expected to lose power relative to treating imbalance as a quantitative phenotype but may be more robust to spurious AS signal.…”
Section: Comparison Of Existing Models With Plasmamentioning
confidence: 99%
“…Lastly, we look at how PLASMA prioritizes experimentally-verified causal variants at GWAS risk loci. Figure 6 shows the strength AS and QTL associations for DPF3 and SCARB1, genes in two kidney GWAS loci that have verified causal variants [23, 33]. At each sample size threshold, the AS statistic more confidently identifies the true causal variant than the QTL statistic.…”
Section: Resultsmentioning
confidence: 99%
“…The StratAS algorithm was used to quantify allele-specific signal and identify initially significant features for fine-mapping [23]. For each peak/gene (the feature) and individual all reads at heterozygous SNPs in the feature were aggregated to compute the haplotype-specific read counts, and summed across the two haplotypes of each individual to compute the QTL read counts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, the risk allele then translates into higher PARP1 levels, which may promote melanoma formation by rescuing cells from BRAF V600E oncogene-induced senescence. Another example involves intronic cis-acting variants in individuals predisposed to breast and ovarian cancer that lead to haploinsufficiency of the DNA repair proteins PALB2 and BRCA1 [ 21 , 22 ], and regions in the genome with differential promoter/enhancer activity between matched tumor and normal samples, that overlap GWAS-associated variants in renal cell carcinoma [ 23 ]. In an instance that exemplifies the complexities of cancer risk and gene regulation, Hua et al identified that prostate cancer risk SNP rs11672691 falls within an intron of lncRNA PCAT19 , in a region with both promoter and enhancer function.…”
Section: Allele-specific Expression In Cancermentioning
confidence: 99%